EFFECT WORK DISCIPLINE, LEADERSHIP AND MOTIVATION ON EMPLOYEE PERFORMANCE - Istyarini, Wiwik (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
Performance is the end result that is the goal in every organization to achieve its goals. Human resources have a very important position considering the performance of the organization is strongly influenced by the quality of its human resources. In addition, high-quality natural resources are useful in adjusting the movement of business climate change so quickly. Work discipline, leadership and motivation are important for a company to increase employee performance. The purpose of this study is to determine the effect of work discipline, leadership, and motivation on employee performance. Associative research method with multiple linear analysis techniques. The study population amounted to 150 respondents, sampling technique used purposive sampling where the number of samples of 60 respondents was calculated using the Slovin formula. The results of the study show that simultaneously work discipline, leadership and motivation have a significant influence on employee performance. Partially only work discipline and leadership have a significant effect, while have no significant motivation on employee performance. Leaders as one of the determinants of direction and organizational goals should be able to control work behaviors and direct them to employee job satisfaction